The sustainable forestry handbook - Higman, Sophie (London : Earthscan, 1999)
"Provides a guide to the practicalities of implementing internationa l standards for sustainable forest management. This highly practical ha ndbook is aimed at forest managers"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Sustainable forestry; Forest management